Crisis leadership using military lessons, organizational experiences, and the power of influence to lessen the impact of chaos on the people you lead - Klann, Gene (Center for Creative Leadership, 2003)
There are actions a leader can take before, during, and after a crisis to effectively reduce the duration and impact of these extremely difficult situations. At its center, effective crisis leadership is comprised of three things -- communication, clarity of vision and values, and caring relationships. Leaders who develop, pay attention to, and practice these qualities go a long way toward handling the human dimension of a crisis. In the end, it's all about the people.
"CCL Stock No. 185"--Title page verso. - Includes bibliographical references. - Description based on print version record
Keywords: Leadership; Crisis management; Gestion de crise